A Mineralized High Strength and Tough Hydrogel for Skull Bone Regeneration. (12th December 2016) - Xu, Bing; Zheng, Pengbin; Gao, Fei; Wang, Wei; Zhang, Hongtao; Zhang, Xuran; Feng, Xuequan; Liu, Wenguang
Abstract : Over the past decade, high strength hydrogels have been intensively investigated. However, developing high strength biofunctional hydrogels for eliciting bone regeneration has been rarely reported. In this work, a mineralized high strength and tough hydrogel is synthesized by one‐step copolymerization of acrylonitrile, 1‐vinylimidazole, and polyethylene glycol diacrylate, followed by in situ precipitation mineralization. It is demonstrated that the CNCN dipole–dipole pairings combined with the interaction of CaP nanocrystals with polymer chains contribute to tremendous increase of tensile/compressive strength, modulus, and fracture energy up to 6.1 MPa, 11.5 MPa, 6.47 MPa, and 7935 J m −2, respectively. The biomineralization is shown to facilitate the attachment and proliferation of C2C12 cells in vitro. This biomineralized hydrogel scaffold is implanted into an 8 mm diameter critical‐size of calvarial defect of rats to evaluate the bone regeneration. 12 week postsurgery results reveal that the mineralized hydrogel exhibits the highest bone volume and density within the defect as measured by computed tomography and histology. This mineralized high strength and tough hydrogel offers a broad range of possibilities to be developed as biofunctional scaffold to promote the reconstruction and regeneration of not only bone, but also load‐bearing connective tissue. Abstract : Mineralized high strength and tough hydrogel is fabricated by one‐step copolymerization of acrylonitrile (dipole interaction monomer), 1‐vinylimidazole, and polyethylene glycol diacrylate, followed by in situ precipitation mineralization. The mineralized hydrogel facilitates the regeneration of skull bone defect, portending its great potential as biofunctional scaffold for eliciting bone regeneration in the future.